Trapped in inactivity? The Austrian social assistance reform in 2019 and its impact on labour supply - Michael Christl; Silvia De Poli (University of Essex, Institute for Social and Economic Research (ISER), 2020)
Financial incentives affect the labour supply decisions of households, but typically the impact of such incentives varies significantly across household types. While there is a substantial literature on the labour supply effects of tax reforms and in-work benefits, the impact of changes in social assistance benefits has received less attention. This paper analyses the impact of the Austrian reform proposal 'Neue Sozialhilfe' ("New Social Assistance"), which was introduced in 2019 and substantially cut social assistance benefits for migrants and families with children. We show that the labour supply effects of these changes in social assistance differ substantially across household types. While women exhibit higher labour supply elasticities in our estimates, the overall effects of the reform are especially strong for men and migrants. Couples with children and migrants, i.e. the groups which were hit the hardest by the reform's social assistance reductions , show the strongest labour supply reactions to the 'New Social Assistance'. Furthermore , we show that overall the reform has a positive, but small, effect on the intensive margin of labour supply.
Keywords: H53; J22; 330; social assistance; reform; labour supply; discrete choice; microsimulation; EUROMOD